Download presentation
Presentation is loading. Please wait.
1
Lake Zurich High School
Parent Graphs with translations By: Jeffrey Bivin Lake Zurich High School Last Updated: November 21, 2005
2
y =|x| Jeff Bivin -- LZHS
3
y = |x+1| + 2 x+1 = 0 x = -1 2 1 Jeff Bivin -- LZHS
4
y = |2x+5| - 4 2x+5 = 0 x = -(5/2) 4 5/2 squeeze squeeze Slope: -2
Jeff Bivin -- LZHS
5
y = 2 |x - 3| + 1 x - 3 = 0 x = 3 1 3 stretch stretch Slope: 2
Jeff Bivin -- LZHS
6
y = 3 |2x - 3| - 4 2x - 3 = 0 x = 3/2 4 stretch stretch 3/2 squeeze
Slope: -3(2) = -6 Slope: 3(2) = 6 Jeff Bivin -- LZHS
7
y = [ x ] x = 0 1 1 Note: y = x Length = 1/1 = 1 Start: (0, 0)
Height = 1 Note: y = x Jeff Bivin -- LZHS
8
y = [ x+1] + 2 x+1 = 0 1 1 x = -1 1 2 Note: y = (x + 1) + 2 y = x + 3
Length = 1/1 = 1 1 Start: (-1, 2) Height = 1 2 Note: y = (x + 1) + 2 y = x + 3 Jeff Bivin -- LZHS
9
y = 3[(½)x] stretch stretch stretch stretch Note: y = 3( (1/2)x )
Length = 1/(1/2) = 2 stretch stretch Height = 3 Start: (0, 0) stretch stretch Note: y = 3( (1/2)x ) y = (3/2)x Jeff Bivin -- LZHS
10
y = -2[ x+1]+3 1 x+1 = 0 x = -1 1 stretch stretch 3 Note:
Length = 1/1 = 1 Start: (-1, 3) 1 Height = -2 stretch stretch 3 Note: y = -2(x + 1) + 3 y = -2x + 1 Jeff Bivin -- LZHS
11
y = [ |x| ] Jeff Bivin -- LZHS
12
y = | [x] | y = [ x ] Jeff Bivin -- LZHS
13
y = | [x] | y = | x | Jeff Bivin -- LZHS
14
f(x) = x2 Jeff Bivin -- LZHS
15
f(x) = (x - 3)2 + 1 x - 3 = 0 x = 3 3 1 Jeff Bivin -- LZHS
16
f(x) = (x + 2)2 - 4 x + 2 = 0 x = -2 2 4 Jeff Bivin -- LZHS
17
f(x) = 2(x - 3)2 - 1 x - 3 = 0 x = 3 3 1 stretch stretch
Jeff Bivin -- LZHS
18
Jeff Bivin -- LZHS
19
x - 2 = 0 x = 2 3 2 Jeff Bivin -- LZHS
20
x + 3 = 0 x = -3 3 4 Jeff Bivin -- LZHS
21
f(x) = x3 Jeff Bivin -- LZHS
22
f(x) = (x-4)3 - 2 x - 4 = 0 x = 4 4 2 Jeff Bivin -- LZHS
23
f(x) = -(x + 2)3 -1 x + 2 = 0 flip x = -2 2 1 Jeff Bivin -- LZHS
24
Jeff Bivin -- LZHS
25
x - 4 = 0 x = 4 y = 2 4 2 x = 4 Jeff Bivin -- LZHS
26
x + 2 = 0 y = 3 x = -2 2 3 x = -2 Jeff Bivin -- LZHS
27
flip x - 3 = 0 x = 3 y = 1 3 1 x = 3 Jeff Bivin -- LZHS
28
f(x) = 2x Jeff Bivin -- LZHS
29
f(x) = 2x-3 x - 3 = 0 x = 3 (3, 1) 3 Jeff Bivin -- LZHS
30
f(x) = 2x+2 - 3 x + 2 = 0 x = -2 3 2 y = -3 (-2, -2)
Jeff Bivin -- LZHS
31
f(x) = 2-x (0, 1) Jeff Bivin -- LZHS
32
f(x) = -(2)-x+4 – 2 -x + 4 = 0 x = 4 4 2 y = -2 flip (4, -3)
Jeff Bivin -- LZHS
33
y = g(x) Jeff Bivin -- LZHS
34
y = g(x-3) - 2 x - 3 = 0 x = 3 3 2 Jeff Bivin -- LZHS
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.